2017
DOI: 10.18378/rebes.v7i1.4858
|View full text |Cite
|
Sign up to set email alerts
|

Percepção do enfermeiro acerca do uso de equipamentos de proteção individual em hospital paraibano

Abstract: Resumo: Biossegurança ou segurança biológica é um conjunto de ações voltadas à prevenção e proteção do trabalhador. Uma estratégia utilizada como forma de evitar contaminação no ambiente de trabalho se dar a partir do uso de Equipamentos de Proteção Individual (EPIs). Objetivou-se analisar a percepção do enfermeiro sobre o uso e importância do EPI diante da assistência aos pacientes. O trabalho trata-se de um estudo do tipo exploratório-descritivo, com abordagem quantiqualitativa, foi realizado com enfermeiros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
2
0
9
Order By: Relevance
“…It is also noteworthy that this measure is recognized as the most effective in preventing HCRI. 15 It is recommended, regarding the location of choice for performing the venipuncture, in Pediatrics, when the venous network is preserved, the selection of the vessel with the greatest probability of duration of all the prescribed therapy, considering, thus, the veins of the hand, forearm and arm (armpit region), as well as avoiding the anti-cubital area 8 . The same was followed by the research professionals, in which the majority preferred upper limbs and reported that, in the correct sequence, the ideal is to choose the veins of the hand first.…”
Section:  Catheter Removalmentioning
confidence: 99%
“…It is also noteworthy that this measure is recognized as the most effective in preventing HCRI. 15 It is recommended, regarding the location of choice for performing the venipuncture, in Pediatrics, when the venous network is preserved, the selection of the vessel with the greatest probability of duration of all the prescribed therapy, considering, thus, the veins of the hand, forearm and arm (armpit region), as well as avoiding the anti-cubital area 8 . The same was followed by the research professionals, in which the majority preferred upper limbs and reported that, in the correct sequence, the ideal is to choose the veins of the hand first.…”
Section:  Catheter Removalmentioning
confidence: 99%
“…16 As far as institutional processes are concerned, training is a tool used to inform employees about the risks they are exposed to in their work environment, generally the need for training is demonstrated when there is a gap between what is required of an employee to comply his assignments or routines in a competent way and what he knows in fact and what enables him to do so. 17 Bureaucracy was cited as a motivating factor for accidents. Study also identified this factor as the most cited motif.…”
Section: Notementioning
confidence: 99%
“…Diante disso, os profissionais que atuam na APS, estão em risco de contaminação pelo COVID-19, quando entram em contato direto com fluidos, secreções e eliminações corporais dos usuários dos serviços. Dentre as medidas de prevenção possíveis, estão as Precauções Padrão com o uso racional dos Equipamentos de Proteção Individual (EPI), garantindo assim a segurança dos atendimentos, evitando complicações de saúde, protegendo a si, aos usuários e suas famílias (Barbosa, Ferreira, Martins, Bezerra & Bezerra, 2017).…”
Section: Introductionunclassified
“…É amplamente reconhecido que quando os profissionais não adotam as medidas preventivas estão mais suscetíveis e vulneráveis aos riscos de contaminação. Estudos destacam dentre as possíveis causas para este comportamento de risco: a fragilidade no conhecimento acerca do uso correto do EPI, bem como na falta de capacitações; a falta de cultura ou resistência quanto ao uso pela dificuldade de adaptação; a desmotivação pela sobrecarga de trabalho; a ideia de cuidar do outro antes de cuidar de si; e o acesso restrito ou Research, Society and Development, v. 9, n. 8, e324985207, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i8.5207 a disponibilização inadequada por parte dos gestores (Barbosa et al, 2017;Nazario, Camponogara & Dias, 2017;llapa-Rodríguez et al, 2018).…”
Section: Introductionunclassified